Effects of sowing date and intercropping on yield, yield components and oil content of sunflower and groundnut in a desert environment in northern Sudan - Hammad, Ammar W. Hammad W.; Mohamed, Ibrahim E; Idris, Siddig E (Gezira Journal of Agricultural Science; Vol 15 No 1 (2017), 2017)
The summer season in the Northern State, Sudan, is characterized by its limited field activities. The present and future expansion of agricultural production is targeted in desert plain soils away from the River Nile bank. This study was conducted during seasons 2014/15 and 2015/16 with the objectives of determining the effects of sowing date and intercropping system on yield, yield components and oil content of sunflower and groundnut. Split-plot design with randomized complete arrangement with four replicates was used. The main plots were assigned to the three sowing date namely: 1 st June, 1 st July and 1 st August. The sub-plots were assigned to intercropping system: viz : sole cropped and intercropping (two rows of groundnut alternate with two rows of sunflower). The interaction between sowing date and intercropping had a significant (p ≤ 0.05) effect on yield component, total yield and oil content of both crops in both seasons. The highest seed yield was obtained by intercropped sunflower and sole groundnut for 1 st June and 1 st August, respectively. The highest oil content was attained by intercropped groundnut and sole sunflower, respectively, for 1 st August.  First June sowing date resulted in the best land equivalent ratio in both seasons. Based on these results, to obtain high seed yield of high oil content, it could be recommended that 1 st of June and 1 st of August were optimum sowing dates for sunflower and groundnut, respectively in the desert environment of north Sudan. It was also recommended to intercrop sunflower with groundnut and sow them on the first of June for the highest LER.   النشاط الزراعي محدود جدا في الموسم الصيفي بالولاية الشمالية في السودان.  وأن التوسع الحالي والمستقبلي في الرقعة الزراعية يستهدف أراضي السهل الصحراوي والتروس العليا البعيدة عن حوض نهر النيل. نفذت هذه التجربة في المناخ الجاف علي تربة السهل الصحراوي في الولاية الشمالية في الموسم الصيفي 2014/15 و2015/16 بهدف تحديد أثر تاريخ الزراعة ونظام الزراعة البينية علي الإنتاجية ومكوناتها وكمية الزيت لمحصولي زهرة الشمس والفول السوداني. نظمت المعاملات إحصائيا باستخدام تصميم القطع المنشقة مع القطاعات العشوائية الكاملة بأربعة مكررات. حيث وضع في القطع الرئيسية ثلاثة تواريخ زراعة (1/6 و1/ 7 و1/8) وفي القطع الثانوية نظام الزراعة البينية: حيث زرع المحصول الواحد بمفرده والمحصولين مع بعض في زراعة بينية (صفان من الفول السوداني يَتناوبانِ مع صفين من زهرة الشمس). أظهرت النتائج أن التداخل بين تاريخ الزراعة والزراعة البينية كان له تأثير معنوي على مكونات الإنتاج والإنتاجية وكمية الزيت لكلا المحصولين في كلا الموسمين. أعلى إنتاجية بذور تحققت للزراعة البينية لزهرة الشمس ولمحصول الفول السوداني منفردا عند زراعتهما في تواريخ الأول من يونيو والأول من أغسطس على التوالي. أعلى نسبة زيت تحققت لمحصولي زهرة الشمس منفردا وللزراعة البينية للفول السوداني عند ما نفذت الزراعة بتاريخ الأول من أغسطس. قيمة مؤشر نسبة الأرض المكافئ أعلي من الرقم واحد في كل تواريخ الزراعة، وتاريخ أول يونيو أعطي أفضل مكافئ في الموسمين علي التوالي. للحصول على أعلى إنتاجية بذور ونسبة زيت لمحصولي زهرة الشمس والفول السوداني توصي الدراسة بأن الأول من يونيو  والأول  من أغسطس هي الأمثل لزراعة محصولي زهرة الشمس والفول السوداني علي التوالي في البيئة الصحراوية بشمال السودان, كما توصي أيضا بأن الزراعة البينية لزهرة الشمس والفول السوداني في أول يونيو هي الأفضل في استغلال الأرض.